Mediterranean farmers’ understandings of ‘good soil management’ and ‘good farmer’ identity in the context of conservation agriculture - Emmeline Topp; Ana Stephan; Elsa Varela; Harun Cicek; Tobias Plieninger (International Journal of Agricultural Sustainability, 2024)
Mediterranean agriculture is increasingly threatened by soil degradation and climate change. Conservation agriculture (CA) is a farming approach characterized by reduced soil disturbance, soil cover, and crop rotation that provides agronomic, economic, and environmental benefits to farmers, but which is not yet widespread in the Mediterranean region. To investigate the sociocultural aspects of CA adoption, we examined farmers’ understandings of ‘good soil management’ and a ‘good farmer’ identity. We employed network analysis to visualize and compare farmers’ mental models of these concepts and how they differed according to farmers’ tillage practices. We found that crop rotation is a prominent concept cognitively tied to fertilizer application, bridging conventional and reduced tillage practices. CA farmers’ mental models of soil management are more complex than conventional farmers’. Demonstrating productivity and having experience and knowledge were the most prominent aspects of farmers’ understanding of a ‘good farmer’. For CA farmers, this was tied to environmental responsibility and innovation, whereas for conventional farmers, a set of best practices including tillage and the use of mineral fertilizers, was valued more highly. CA may compete with held understandings concerning soil management among conventional farmers. CA adoption programmes could be better tailored to align with their cultural values.